Construyendo una carroza carnavalesca: transmisión de saberes tradicionales en el proceso de elaboración de carrozas en el carnaval de negros y blancos de pasto, Nariño, Colombia - Nieves Gil, Luis Eduardo (Universidad Antonio Nariño, 2023)
“Burlesque”, “Blanco Carnaval”, “Mil Colores”, “Soberbia”, “Survivir”, “Principio y Fin”, “Despojos”, “King de Carnavales”, “Qué raraca reyes”, “Spirit of the jungle” , "Nature is my house", "The Carnival King", "Extinction, crying of the earth", "The bad hour", "Yucuruna and the four elements", "Dream", "The Golden Jaguar", "Abya Yala” and “El Colorado”. Names of the nineteen motorized floats that on January 6, 2018 were present through the main streets of Pasto, capital of the department of Nariño. They express the memory and identity of the Pasto people.